Alleviation of oxidative stresses by potassium fertilizer in spring maize under early and late sown conditions - Ahmad, I; Basra, SMA; Akram, M; Wasaya, Allah; Hussain, SA; Iqbal, Asif (Bangladesh Journal of Scientific and Industrial Research, 2016)
The yield potential of spring planted maize is much higher than autumn crop. Heat stress at during anthesis and grain formation stage is one of the main hindrances in its spring cultivation especially under late sown conditions but early sowing seems an ideal solution to escape from heat spell which may cause poor stand establishment. Both temperature extremes cause oxidative stresses and potassium application may lessen the damage. The present paper aims to contribute the role of potassium application in alleviation of oxidative damage and improvement in stress tolerance of early and late sown spring maize. The experiment was carried out in randomized complete block design (RCBD) with split plot arrangement randomizing the sowing dates Early, Mid and Late in main plots and potassium levels K0 (0), K1 (100) and K2 (200 kg ha-1) in sub-plots. Data on growth parameters were recorded fortnightly starting from 30 to 90 days after sowing by using standard procedure while relative water and chlorophyll contents, peroxidase (POD) and catalase (CAT) activities were measured at both tasselling and blister stage. Growth was reduced under both early and late sown conditions but potassium application improved it by enhancing antioxidants defense system which protects leaf chlorophyll contents under early and late sown conditions. Furthermore, antioxidants like CAT and POD activities were increased while SOD/[POD+CAT] were decreased with increase in potassium and age. It is suggested that 100 kg ha-1 potassium reduced oxidative damage and improved stress tolerance of spring maize Bangladesh J. Sci. Ind. Res. 51(2), 101-110, 2016